Measurement of beauty-strange meson production in Pb–Pb collisions at sNN=5.02TeV via non-prompt Ds+ mesons - Acharya, S.; Adamovã, D.; Adler, A.; Aglieri Rinella, G.; Agnello, M.; Agrawal, N.; Ahammed, Z.; Ahmad, S.; Ahn, S.U.; Ahuja, I.; Akindinov, A.; Al-Turany, M.; et al. (Elsevier, 2023)
The production yields of non-prompt D+ s mesons, namely D+ s mesons from beauty-hadron decays, were measured for the first time as a function of the transverse momentum (pT) at midrapidity (|y| < 0.5) in central and semi-central Pb–Pb collisions at a centre-of-mass energy per nucleon pair √sNN = 5.02 TeV with the ALICE experiment at the LHC. The D+ s mesons and their charge conjugates were reconstructed from the hadronic decay channel D+ s → φπ+, with φ → K−K+, in the 4 < pT < 36 GeV/c and 2 < pT < 24 GeV/c intervals for the 0–10% and 30–50% centrality classes, respectively. The measured yields of non-prompt D+ s mesons are compared to those of prompt D+ s and non-prompt D0 mesons by calculating the ratios of the production yields in Pb–Pb collisions and the nuclear modification factor RAA. The ratio between the RAA of non-prompt D+ s and prompt D+ s mesons, and that between the RAA of non-prompt D+ s and non-prompt D0 mesons in central Pb–Pb collisions are found to be on average higher than unity in the 4 < pT < 12 GeV/c interval with a statistical significance of about 1.6 σ and 1.7 σ, respectively. The measured RAA ratios are compared with the predictions of theoretical models of heavy-quark transport in a hydrodynamically expanding QGP that incorporate hadronisation via quark recombination
Keywords: Physics; Meson; Production (economics); Hadron; Particle physics; Nuclear physics; https://purl.org/pe-repo/ocde/ford#1.03.04